Uma experiência de dramatização com alunos de enfermagem - Goulart, Silvéria Ferreira (1979)
Experimental work. ln its accomplishment a group of students were used to dramatize nursing during six weeks. ln this approach we intended to verify what difficulties were lived by the students at the beginning of the professional cycle. The best of relationship in their personal contact with coleagues, teachers and school, good as in their perspectives of the profession in the future was expected to happen at the end of the experience. The limits of the results concerned the small number of meetings and the fact that the experience had not been extended to all the students of the group. And, although the initial hypothesis had been rejected, the utilization of dramas, in similar situations as written in this work, is amply indicated, since limitations inside this study were overcome.